Glycan modification of glioblastoma‐derived extracellular vesicles enhances receptor‐mediated targeting of dendritic cells. Issue 1 (9th August 2019) - Dusoswa, Sophie A.; Horrevorts, Sophie K.; Ambrosini, Martino; Kalay, Hakan; Paauw, Nanne J.; Nieuwland, Rienk; Pegtel, Michiel D.; Würdinger, Tom; Van Kooyk, Yvette; Garcia‐Vallejo, Juan J.
ABSTRACT: Glioblastoma is the most prevalent and aggressive primary brain tumour for which total tumour lysate‐pulsed dendritic cell vaccination is currently under clinical evaluation. Glioblastoma extracellular vesicles (EVs) may represent an enriched cell‐free source of tumour‐associated (neo‐) antigens to pulse dendritic cells (DCs) for the initiation of an anti‐tumour immune response. Capture and uptake of EVs by DCs could occur in a receptor‐mediated and presumably glycan‐dependent way, yet the glycan composition of glioblastoma EVs is unknown. Here, we set out to characterize the glycocalyx composition of glioblastoma EVs by lectin‐binding ELISA and comprehensive immunogold transmission electron microscopy (immuno‐TEM). The surface glycan profile of human glioblastoma cell line‐derived EVs (50–200 nm) was dominated by α‐2, 3‐ and α‐2, 6 linked sialic acid‐capped complex N ‐glycans and bi‐antennary N ‐glycans. Since sialic acids can trigger immune inhibitory sialic acid–binding Ig‐like lectin (Siglec) receptors, we screened for Siglec ligands on the EVs. Glioblastoma EVs showed significant binding to Siglec‐9, which is highly expressed on DCs. Surprisingly, however, glioblastoma EVs lack glycans that could bind Dendritic Cell‐Specific Intercellular adhesion molecule‐3‐Grabbing Non‐integrin (DC‐SIGN, CD209), a receptor that mediates uptake and induction of CD4 + and CD8 + T cell activation. Therefore, we explored whether modification of the EV glycan surface could reduce immune inhibitory Siglec binding, while enhancing EV internalization by DCs in a DC‐SIGN dependent manner. Desialylation with a pan‐sialic acid hydrolase led to reduction of sialic acid expression on EVs. Moreover, insertion of a high‐affinity ligand (Lewis Y ) for DC‐SIGN resulted in a four‐fold increase of uptake by monocyte‐derived DCs. In conclusion, we show that the glycocalyx composition of EVs is a key factor of efficient DC targeting and that modification of the EV glycocalyx potentiates EVs as anti‐cancer vaccine.